2018
DOI: 10.4038/jas.v14i1.8455
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Characterization and Genetic Diversity Assessment of the Rhizobial Populations Inhabiting <em>Gliricidia sepium</em> in selected Locations of Ampara District, Sri Lanka

Abstract: Purpose: Gliricidia sepium is a wide spread multipurpose legume plant which is effective in nitrogen fixation and host to many Rhizobial strains. However, few studies have been carried out to identify and characterize the Rhizobial populations inhabiting G. sepium in Sri Lanka. The main objective of this study was to isolate and identify the stress tolerant Rhizobial strains in G. sepium. Research Method: Root nodules of G. sepium were collected from seven locations in Ampara district, which belongs to dry zon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…But there is no relationship between the sampling site and rhizobial strains. Nawanjana and Rajapakse, (2018) have reported that there is a high genetic diversity of rhizobia in G. sepium from Ampara district, Sri Lanka. Similarly, the present study provides further evidence for the fact that a diverse group of stress tolerant rhizobia inhabits G. sepium in dry zone soils, Sri Lanka.…”
Section: Discussionmentioning
confidence: 99%
“…But there is no relationship between the sampling site and rhizobial strains. Nawanjana and Rajapakse, (2018) have reported that there is a high genetic diversity of rhizobia in G. sepium from Ampara district, Sri Lanka. Similarly, the present study provides further evidence for the fact that a diverse group of stress tolerant rhizobia inhabits G. sepium in dry zone soils, Sri Lanka.…”
Section: Discussionmentioning
confidence: 99%